Ácidos fenólicos e aminas bioativas livres e conjugadas em sorgo: teores e atividade antioxidante - Caroline Liboreiro Paiva (2014)
This work aimed to evaluate the conditions of sorghum bioactive amines extraction, identify the profile and levels of phenolic acids, and free and conjugated bioactive amines in sorghum genotypes and to evaluate the antioxidant activity of these compounds. The best conditions for the extraction of free amines from sorghum were 420 m particle size and 3 consecutive extractions with 5% TCA. Only PUT, CAD, SPD and SPM were detected in sorghum and the levels of polyamines detected indicated that this cereal is a significant source of polyamines, mainly in sorghum grown under normal hydric conditions. After seven days of sorghum germination, the levels of PUT increased significantly, SPD remained constant and SPM was detected in cotyledon and radicle of some genotypes. It was also found that the changes on the levels of amines during germination were not affected by the presence of tannin in the grain. Among phenolic acids investigated, coumaric and ferulic acids were present in all studied lines, ferulic being the prevalent. More than 90% of the hydroxycinnamic acids were present in the pericarp. In relation to conjugated amines, derivatives of SPM were prevalentt, followed by derivatives of SPD. Some genotypes of sorghum showed significant antioxidant activity by means of DPPH, ABTS and Rancimat®. For irrigated sorghum, the changes on the levels of phenolic acids in the soluble fraction affected significantly the levels of free amines in these grains. Linear regression studies indicated that when SPD levels increased, the levels of the corresponding diferulic and dicoumaric amides also increased.